Wireless based home security with automation system - Wan Norziela, Wan Rosli (2010)
The aim of the project is to design a wireless based home security with automation system. The system uses wireless technology to revolutionize the standards of living which could give assurance for user to protect their homes from burglars, thieves and criminals. This project is so versatile and is equipped with various sensors such as passive infrared sensor, magnetic switch sensor and vibration sensor to detect different forms of intrusion. A microcontroller is used to control the system operation while a remote gadget is used to arm and disarm the system. To ensure only the authorized user can operate the system, the gadget is equipped with a password. Various indication outputs such as BUZZER, LED and LCD are used to display the alarm status. In addition, the sound indicators like siren are also included in the design to inform intrusion. Due to the consideration of user-friendliness, portability as well as wider-area coverage, all the sensors and remote gadget are implemented using zigbee transceiver. A backup battery module is also introduced in the design to ensure the system keep functioning even during power failure.